Teaching English For Specific Purposes (Esp): Methods And Challenges - Sevara Shermatova; Gulsevar Usmonova (Euro Asian Journal Publishing, 2025)
English for Specific Purposes (ESP) is crucial in preparing learners for professional communication across various fields, such as business and engineering. However, selecting and implementing effective teaching methodologies remains a persistent challenge. This study investigates the effectiveness of three widely used ESP teaching methods: the Communicative Approach (CA), Task-Based Learning (TBL), and Content-Based Instruction (CBI), while also identifying key challenges faced by educators and learners. A mixedmethods approach was employed, incorporating surveys, interviews, and test result analysis to assess the impact of these methodologies. Findings indicate that TBL significantly enhances practical language application, whereas CBI fosters a deeper understanding of subject-specific content. However, educators face challenges such as a lack of specialized teaching materials, student motivation issues, and varying proficiency levels among learners. Additionally, limited institutional support further exacerbates these difficulties. The study offers insights into overcoming these barriers and provides recommendations for enhancing ESP instruction in higher education
Keywords: English for Specific Purposes; language teaching methods